Rancang Bangun Sistem Informasi Penjualan Barang Interior Berbasis Web pada PT. Jesindo Prima Sejati - Ridho Alvin Setiawan; A.B. Tjandrarini; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. Jesindo Prima Sejati is a company engaged in the sale of interior goods and been establish since 1990. The marketing process is currently done by door to door and over the phone, which caused less extensive marketing reach. The process of ordering and payment is recorded in the book so that the administration had difficulty in searching the required data. The customer is not able to monitor the status of orders and the company owner difficulty in obtaining information related to the sale. Based on the existing problems, then PT. Jesindo Prima Sejati requires web-based sales information system. Sales information system that is built has a function to record and store the necessary data and produce information and reports related to the sale. Sales information system also provides notification through the system, email, and SMS. The reports is needed, is a report of the sale, report of accounts receivable, report of goods most often ordered, report of sales volume per goods per period, report of goods most ordered by region, report of goods most ordered per customer and the report of the history per customer. Sales information system also generates notifications about the price offer, payment, invoice, order completion and delivery of goods. Based on the results of system testing performed together with PT. Jesindo Prima Sejati, This system can help PT. Jesindo Prima Sejati and consumers. It is proof by the results of system testing conducted and results of data processing by 88% which is included in the excellent category.